A exigibilidade do direito à educação no Brasil - Negrão, Mário Márcio (2017)
The right to an education is the result of a series of norms that encompass a variety of hierarquical structures such as federal, municipal and state laws as well as ordinances and regimens designed to discipline the relations between those involved in the educational process. The principles, which guide these legal structures, organize the relations between pupils, teachers, administrators’ specialists and technicians involved in a direct as well as indirect manner in the realm of Brazilian education. This thesis fundaments itself on the principle of human dignity proclaimed constitutionally in a democratic state of law concerned with the right to an education. Constructed as a bibliographical investigation dedicated to the right to an education, the perspective of legal effectiveness with regard to the constitutional protection essential to the realization of fundamental human rights is a guiding principle. It is a well-known fact that the right belonging to any citizen to a full education with quality constitutes a social right demandable by anyone. To this regard, this thesis investigates the possibility of the usefulness of those resources that are useful in demanding social rights such as the right to an education belonging to anyone as well as the possibility of their immediate application in the light of their violation or omission. Together with this, this investigation explores in a systematic way the efficacy and effectivity of Brazilian laws concerning the right to an education bearing in mind several theories of fundamental rights. The conclusion is that the demand for the legitimacy and effectiveness brings to light a new legal phenomenon which pertains to the role of the judiciary which comes to light when educational laws are omitted or violated, denying to the citizens a just, solidary education with quality. On the other hand, when guarantees are in question, it is possible that the political and social sphere would be more useful in resolving such demands instead of measures located exclusively in the realm of jurisprudence.